2013
DOI: 10.1002/phy2.185
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory role of androgenic and estrogenic neurosteroids in determining the direction of synaptic plasticity in the CA1 hippocampal region of male rats

Abstract: Estrogenic and androgenic neurosteroids can rapidly modulate synaptic plasticity in the brain through interaction with membrane receptors for estrogens (ERs) and androgens (ARs). We used electrophysiological recordings in slices of young and adolescent male rats to explore the influence of sex neurosteroids on synaptic plasticity in the CA1 hippocampal region, by blocking ARs or ERs during induction of long‐term depression (LTD) and depotentiation (DP) by low‐frequency stimulation (LFS) and long‐term potentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 59 publications
5
32
1
Order By: Relevance
“…The modulatory role of neurosteroid E2 on synaptic plasticity has been demonstrated in vestibular nuclei, basal ganglia and hippocampus by acute as well as long-lasting inhibition of the E2 pathway, which impairs LTP induction (Grassi et al 2009a(Grassi et al , b, 2010(Grassi et al , 2012Pettorossi et al 2013;Scarduzio et al 2013;Vierk et al 2012Vierk et al , 2014. Consistent with these findings, it has been shown that acute inhibition of E2 synthesis also exerts rapid effects on spatial learning, working memory and fear extinction (Alejandre-Gomez et al 2007;Graham and Milad 2014;Moradpour et al 2006).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The modulatory role of neurosteroid E2 on synaptic plasticity has been demonstrated in vestibular nuclei, basal ganglia and hippocampus by acute as well as long-lasting inhibition of the E2 pathway, which impairs LTP induction (Grassi et al 2009a(Grassi et al , b, 2010(Grassi et al , 2012Pettorossi et al 2013;Scarduzio et al 2013;Vierk et al 2012Vierk et al , 2014. Consistent with these findings, it has been shown that acute inhibition of E2 synthesis also exerts rapid effects on spatial learning, working memory and fear extinction (Alejandre-Gomez et al 2007;Graham and Milad 2014;Moradpour et al 2006).…”
Section: Introductionsupporting
confidence: 71%
“…These results are supported by previous data showing the rapid effects of inhibition of aromatase on synaptic LTP in other systems. Indeed, in hippocampus and striatum the same LTZ dose we used here prevented or remarkably reduced LTP, while in vestibular nuclei LTP was inverted in LTD without affecting the basal synaptic responses and LTD (Grassi et al 2009a(Grassi et al , b, 2010(Grassi et al , 2012Pettorossi et al 2013). …”
Section: Neurosteroid E2 Regulates Ltp In Acute Cerebellar Slicesmentioning
confidence: 99%
“…Grassi, Pettorossi and co-workers showed that under blocking of ER by ICI, an additional inhibition of AR by flutamide induced moderate LTP (upon repetitive tetanus stimulation of 4 sets of 100 Hz, 1 s) in the developing CA1 hippocampal slices from postnatal 2-3 weeks-old rats (Pettorossi et al, 2013). This means that AR may have suppressive effects on LTP.…”
Section: Difference and Similarity In Synaptic Effects Between Androgmentioning
confidence: 95%
“…This means that AR may have suppressive effects on LTP. Only AR antagonist, however, does not suppress LTP upon repetitive tetanus stimulation (Pettorossi et al, 2013). Suppressive effects by DHT on LTP are also suggested for CA3 mossy fiber.…”
Section: Difference and Similarity In Synaptic Effects Between Androgmentioning
confidence: 95%
“…Grassi, Petorrossi and co-workers (Pettorossi et al, 2013) show that blocking androgen receptor AR by flutamide converts LTD (upon low frequency electric stimulation) to LTP in very young hippocampal slices (two to three week old) and in adolescent hippocampal slices (seven week-old). They show that blocking estrogen receptor ER by ICI suppresses LTP, but not affects LTD.…”
Section: Age Dependent Difference In Ltd Modulation By Estradiolmentioning
confidence: 97%